The role of the neighbourhood for firms that stayed- or left - Bart Sleutjes (European Regional Science Association (ERSA), 2010)
This paper looks at the factors that influence an entrepreneur's decision to stay or move out of a neighbourhood. In general, new and relatively small firms tend to have a strong connection to their local environment and hardly ever move across large distances. In the Netherlands, 75% of all moving firms even stays within the same municipality, to business parks or to other neighbourhoods (RPB, 2007). Aspects of the building (e.g. size) are the most likely reason to move, but does the neighbourhood itself matter as well? We look to what extent neighbourhood aspects influence or have influenced the decision to stay or move, both on the push and the pull side. These aspects may be related to the local physical environment or the safety situation, but also to the local social community. There is recent evidence that localized firm support network contacts contribute positively to firm success (Sleutjes & Schutjens, 2009). Local personal and professional relationships may tie firms to their local environment. If certain neighbourhood characteristics or localized networks turn out to be pull or push factors for entrepreneurs, this might interest policy makers aiming at stimulating the neighbourhood economy by attracting and retaining entrepreneurs within certain urban neighbourhoods. Basically, three questions will be answered in this paper: 1. To what extent do social and physical neighbourhood characteristics play a role in a firm's decision to stay or move? 2. How do localized firm support networks influence a firm's decision to stay put within a certain neighbourhood or not? 3. To what extent do moving firms keep in touch with local network contacts from their former neighbourhood? We conducted in-depth semi-structured interviews among 40 entrepreneurs from five similar Dutch neighbourhoods. The sample is equally divided between firms that stayed and firms that recently moved out of the neighbourhood (20/20). The survey provides detailed information on the characteristics and the performance of firms, as well as network contacts, neighbourhood attachment, location choice, and the valuation of location aspects. We make use of qualitative methods in order to analyze our data.
Keywords: 330